Cooling-Off in Negotiations - Does It Work? - Jörg Oechssler; Andreas Roider; Patrick W. Schmitz (University of Heidelberg, Department of Economics, 2009)
Negotiations frequently end in conflict after one party rejects a final offer. In a large-scale internet experiment, we investigate whether a 24-hour cooling-off period leads to fewer rejections in ultimatum bargaining. We conduct a standard cash treatment and a lottery treatment, where subjects receive lottery tickets for several large prizes - emulating a high-stakes environment. In the lottery treatment, unfair offers are less frequently rejected, and cooling-off significantly reduces the rejection rate further. In the cash treatment, rejections are more frequent and remain so after cooling-off. This treatment difference is particularly pronounced for subjects with lower cognitive abilities.
urn:nbn:de:bsz:16-opus-94641
Keywords: C78; C99; D8; 330; negotiations; ultimatum game; emotions; cooling-off; cognitive abilities; behavioral biases; internet experiment; Verhandlungen; Konflikt; Verhaltensökonomik; Emotion; Zeit; Spieltheorie